Advice over empathy: a national cross-sectional examination of communication in United States dietetic education - Ashlea Braun; Sarah Corcoran; Gena Wollenberg; Kristen McClanahan; Rachel Liebe; Michael Businelle; Jillian Joyce (BMC Medical Education)
Abstract Background Empathy is an important element of patient communication and is well operationalized in established approaches to one-on-one communication, such as motivational interviewing (MI). The accurate demonstration of empathy is especially important when seeking to facilitate a change in behavior, such as in lifestyle or diet, given these issues often involve psychological barriers versus knowledge deficits. Registered dietitians are a key licensed healthcare provider tasked with facilitating changes in diet, but the extent to which current educational standards in the United States (US) contribute to cultivation of empathy as a professional skill has not been systematically evaluated. The objective of this study was to characterize therapeutic empathy and communication among US dietetics students. Methods A cross-sectional survey-based study was conducted among US-based dietetics students, recruited via forwarded e-mail messages from directors of accredited programs. Personal characteristics and responses to the Helpful Responses Questionnaire (HRQ)– a validated measure of therapeutic empathy– were collected. All HRQ responses (6/participant) were reviewed and scored from 1 to 5 based on the use of reflections and communication roadblocks (1 = least empathetic, 5 = most empathetic) per established methods. One mean total HRQ score was computed per participant and precise roadblocks used were tabulated. Given the distribution of the final data set, a binary variable was created to capture whether participants had a total HRQ score of 1 or > 1. Logistic regression and chi-square tests were used to identify participant attributes associated with achieving scores > 1. Results Participants (n = 506) were mostly white females (95.06% female, 79.05% white). The mean total HRQ score was 1.21 (SD: 0.47), with n = 175 participants (34.6%) achieving a mean total HRQ score > 1. Age, being married, having a previous non-nutrition-related career, or enrollment in a standalone internship were associated with HRQ score > 1 (P ≤ 0.001). The most common roadblock used was advising followed by using logic. Conclusion US-based dietetics students may not be consistently using empathetic communication, instead prioritizing problem-solving-oriented strategies (e.g., giving advice). Exploring optimal strategies to training that facilitate improved empathy, and the relative importance of empathy versus problem-solving strategies in facilitating behavior change, are important next steps. Further, the HRQ was successfully implemented, and its use should be replicated in other regions and populations.